Spiritual Quotient: What Is Its Relationship with Local Cultural Accommodation in Religious Moderation? - Sapitri, Vera; Pratiwi, Anggraini; Wardana, Mochammad Ichsan; Asmara , Dea; Apita , Desma Hemaliyah (Cultura Islamica: Journal of Islamic Studies, Management, and Culture, 2025)
This study aims to analyze the relationship between the internalization of religious moderation values and the spiritual quotient (SQ) of students, with a particular emphasis on the role of local cultural accommodation as a key element. Religious moderation values such as tawasuth, tasamuh, tawazun, and i'tidal are internalized through educational practices and school culture, and are assumed to play a role in shaping the spiritual dimensions of students, including the meaning of life, self-awareness, and transcendental relationships. The study employs a correlational quantitative approach with parametric testing to ensure the validity and significance of the relationship. The results indicate a significant and linear relationship between the internalization of religious moderation values and the students' spiritual quotient. Local cultural accommodation emerges as a strong indicator in bridging religious values with contextual spiritual experiences. The internalization of values through local religious cultural experiences helps students develop a spirituality that is non-dogmatic, yet reflective, inclusive, and transformative. The study recommends the integration of religious moderation values with local culture-based education in the development of religious and character education curricula.